A Secure Connection Management Solution for IPSEC on FPGA - Kỷ, Phan Văn; Phúc, La Hữu (Journal of Science and Technology on Information security, 2022)
Abstract— IPSec (Internet Protocol Security) is a secure protocol aiming to protect data traffic via the Internet. There is a separate set of algorithms and security parameters in each secure connection in the IPSec deployment model. In order to ensure stable connections in high-bandwidth environments, managing multiple secure connections simultaneously on IPSec devices holds a significant role. Due to the complexity of the management process, this is commonly done by software on the operating system. This solution is restricted due to data exchange between field-programmable gate array (FPGA) and microprocessor. In this article, a solution was proposed to organize and manage a confidential connection after using Internet Key Exchange (IKE) to exchange keys for IPSec directly using hardware description language on FPGA, aiming to meet high-speed requirements with many connections.